Integrative literature review of the reported uses of serological tests in leprosy management - Angélica da Conceição Oliveira Coelho Fabri; Ana Paula Mendes Carvalho; Nayara Figueiredo Vieira; Isabela de Caux Bueno; Rayssa Nogueira Rodrigues; Thayenne Barrozo Mota Monteiro; Rodrigo Correa-Oliveira; Malcolm S. Duthie; Francisco Carlos Félix Lana (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: An integrative literature review was conducted to synthesize available publications regarding the potential use of serological tests in leprosy programs. We searched the databases Literatura Latino-Americana e do Caribe em Ciências da Saúde, Índice Bibliográfico Espanhol em Ciências da Saúde, Acervo da Biblioteca da Organização Pan-Americana da Saúde, Medical Literature Analysis and Retrieval System Online, Hanseníase, National Library of Medicine, Scopus, Ovid, Cinahl, and Web of Science for articles investigating the use of serological tests for antibodies against phenolic glycolipid-I (PGL-I), ML0405, ML2331, leprosy IDRI diagnostic-1 (LID-1), and natural disaccharide octyl-leprosy IDRI diagnostic-1 (NDO-LID). From an initial pool of 3.514 articles, 40 full-length articles fulfilled our inclusion criteria. Based on these papers, we concluded that these antibodies can be used to assist in diagnosing leprosy, detecting neuritis, monitoring therapeutic efficacy, and monitoring household contacts or at-risk populations in leprosy-endemic areas. Thus, available data suggest that serological tests could contribute substantially to leprosy management.